2021
DOI: 10.3389/fnagi.2021.674135
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protein Persulfidation in Brain Aging and Neurodegeneration

Abstract: Hydrogen sulfide (H2S), originally considered a toxic gas, is now a recognized gasotransmitter. Numerous studies have revealed the role of H2S as a redox signaling molecule that controls important physiological/pathophysiological functions. The underlying mechanism postulated to serve as an explanation of these effects is protein persulfidation (P-SSH, also known as S-sulfhydration), an oxidative posttranslational modification of cysteine thiols. Protein persulfidation has remained understudied due to its inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 113 publications
(182 reference statements)
0
41
0
1
Order By: Relevance
“…In addition to its direct antioxidant effects, the sulfur atoms of RSS are mobile and act as signaling molecules that regulate various physiological functions through the persulfidation of the SH groups of proteins (Doka et al, 2020;Petrovic et al, 2021;Yang et al, 2020). In fact, several lines of evidence have suggested that the formation of persulfide on cysteine residues in proteins, such as ATP-sensitive potassium (K ATP ) channels (Jiang et al, 2010), transient receptor potential vanilloid 4 channels (Naik et al, 2016), NMDA glutamate receptors (Luo et al, 2019), peroxisome proliferator-activated receptor g (Cai et al, 2016), parkin (Vandiver et al, 2013), dynamin-related protein 1 (Akaike et al, 2017), lactate dehydrogenase A (Untereiner et al, 2017), protein tyrosine phosphatase 1B (Krishnan et al, 2011), p65 (Sen et al, 2012), and Kelch-like ECH-associated protein 1 (Yang et al, 2013), regulates their function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its direct antioxidant effects, the sulfur atoms of RSS are mobile and act as signaling molecules that regulate various physiological functions through the persulfidation of the SH groups of proteins (Doka et al, 2020;Petrovic et al, 2021;Yang et al, 2020). In fact, several lines of evidence have suggested that the formation of persulfide on cysteine residues in proteins, such as ATP-sensitive potassium (K ATP ) channels (Jiang et al, 2010), transient receptor potential vanilloid 4 channels (Naik et al, 2016), NMDA glutamate receptors (Luo et al, 2019), peroxisome proliferator-activated receptor g (Cai et al, 2016), parkin (Vandiver et al, 2013), dynamin-related protein 1 (Akaike et al, 2017), lactate dehydrogenase A (Untereiner et al, 2017), protein tyrosine phosphatase 1B (Krishnan et al, 2011), p65 (Sen et al, 2012), and Kelch-like ECH-associated protein 1 (Yang et al, 2013), regulates their function.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of most Cys chiral sensing methods is at the micromolar level [7] , [8] , [9] , [10] , [11] . In addition, it has been reported that the concentration of Cys in healthy bodies ranges from 15 to 30 μm and elevated levels may indicate disorders in the brain or kidney [1] , [2] , [3] . Thus, the quantitation limit of 10 μmol/L is sufficient for biosensing of chiral Cys.…”
Section: Resultsmentioning
confidence: 99%
“…The dysregulation of L-cysteine (L-Cys) in the brain is related to some neurodegenerative diseases, such as Parkinson’s disease and Alzheimer’s disease [1] , [2] , [3] , whereas D-Cys exerts neuroprotective and therapeutic effects via hydrogen sulfide production from the D-Cys-dependent pathway, which prevents oxidative stress in the brain [4] , [5] , [6] . In recent years, various probes, including molecular sensors [7] , [8] , nanoparticle sensors [9] , [10] , and quantum dot sensors [11] , have been developed to recognize Cys enantiomers based on electronic circular dichroism (ECD) or fluorescent response signals.…”
Section: Introductionmentioning
confidence: 99%
“…It is often suggested that H 2 S diffuses through the extracellular membrane, but at pH 7.4, the large majority of sulfide is ionized as HS − or S 2− [ 39 ], these ions should not diffuse through the cell membrane at the rates observed. Many reports implicate H 2 S as a paracrine signaling agent at an intracellular level (i.e., cysteine persulfidation) as well as extracellular level (extracellular matrix maintenance and remodeling) [ 92 , 93 , 94 ]. However, no intramembrane channel responsible for transporting ionized H 2 S has been identified yet.…”
Section: Discussionmentioning
confidence: 99%